Devida diligência obrigatória em direitos humanos : suas potencialidades multiníveis de combate ao trabalho escravo contemporâneo - Taques, Lécia Nidia Ferreir (2024)
The object of this research is the study of contemporary slavery and its insertion into supply chains, proposing the cogency of human rights due diligence by companies as an additional mechanism to combat this practice. The need to shift the focus from small producers to large companies, in the supply chain model consolidated in recent decades, is the main objective of this dissertation. With this in mind, starting from the premise that decent work is a human right, the study demonstrates the topicality and relevance of debates on corporate duties in this area. The work is based on theoretical research with bibliographic and documentary procedures of doctrine, jurisprudence, official data from the Brazilian government and official research on the subject, case studies, with exploratory, descriptive and comparative research. The combined analysis of the theoretical articulations and the case studies led to the conclusion that the direction of the duty of integrity by the supply chain to the lead company is a construction already present in academic studies and Brazilian jurisprudence. At the moment, there is a need to build a clear legal framework on the obligations of companies, which will generate a virtuous cascade effect and make national policies to eradicate slave labour more efficient by combating this serious violation of human rights preventively and, on a large scale, by establishing a paradigm of labour relations based on human dignity within supply chains.